2023
DOI: 10.1007/s00436-023-07836-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of intestinal parasites by conventional and molecular methods in children with gastrointestinal system complaints

Abstract: Background and aims:Intestinal parasitic infections are a global health problem that causes morbidity and mortality, especially in children living in rural areas. In this study, stool samples of pediatric patients with gastrointestinal complaints were examined by conventional and molecular methods to determine the prevalence of intestinal parasites. Methods:A total of 100 pediatric patients with gastrointestinal complaints and 50 healthy children were included in the study. Stool samples were collected from ea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Of these case-control studies, a very small number identified potential pathogenicity of D. fragilis in association with more frequent gastrointestinal symptoms or diarrhoea in groups carrying the protozoan [ 2 , 28 ]. The vast majority of comparative studies using D. fragilis PCR assays as a diagnostic method demonstrated no statistically significant difference in terms of the frequency of gastrointestinal signs between patients with the parasite in their stools and negative control subjects [ 14 , 16 , 17 , 19 , 20 , 25 , 26 , 31 ], or even a higher incidence of D. fragilis detection in asymptomatic patients than in symptomatic ones [ 3 5 ]. Very recently, in a large study that included nearly 28,000 patients, Shasha et al showed a significantly lower occurrence of digestive symptoms [adjusted OR 0.82 (0.76–0.88)] in patients testing positive for D. fragilis on PCR assay compared to control patients negative for this parasite [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these case-control studies, a very small number identified potential pathogenicity of D. fragilis in association with more frequent gastrointestinal symptoms or diarrhoea in groups carrying the protozoan [ 2 , 28 ]. The vast majority of comparative studies using D. fragilis PCR assays as a diagnostic method demonstrated no statistically significant difference in terms of the frequency of gastrointestinal signs between patients with the parasite in their stools and negative control subjects [ 14 , 16 , 17 , 19 , 20 , 25 , 26 , 31 ], or even a higher incidence of D. fragilis detection in asymptomatic patients than in symptomatic ones [ 3 5 ]. Very recently, in a large study that included nearly 28,000 patients, Shasha et al showed a significantly lower occurrence of digestive symptoms [adjusted OR 0.82 (0.76–0.88)] in patients testing positive for D. fragilis on PCR assay compared to control patients negative for this parasite [ 36 ].…”
Section: Discussionmentioning
confidence: 99%